2021
DOI: 10.3390/molecules26010192
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids Analysis of Habranthus cardenasianus (Amaryllidaceae), Anti-Cholinesterase Activity and Biomass Production by Propagation Strategies

Abstract: Plants in the Amaryllidaceae family synthesize a diversity of bioactive alkaloids. Some of these plant species are not abundant and have a low natural multiplication rate. The aims of this work were the alkaloids analysis of a Habranthus cardenasianus bulbs extract, the evaluation of its inhibitory activity against cholinesterases, and to test several propagation strategies for biomass production. Eleven compounds were characterized by GC-MS in the alkaloid extract, which showed a relatively high proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…These alkaloids were identified comparing their physical (specific optical rotation) and spectroscopic ( 1 H and 13 C NMR and ESI MS) properties with those already reported in the literature: for 1 by Lamoral-Theys et al (2009) [13] isolated from Stenbergia lutea, for 2 with those reported by Antoun et al (1993) [41] and Boit and Döpke (1960) [42] when isolated from Hymenocallis expansa and Hippeastrum aulicum, respectively. Alkaloids As previously reported, haemanthidine (7) was isolated as two 6-epimers [56] in a scalar ratio. The equilibrium between the two epimers was also reported for 6-hydroxycrinamine, but not for closely related crinine-type alkaloids such as 6α-hydroxycrinine and 6αhydroxybuphonisine.…”
Section: Resultssupporting
confidence: 59%
“…These alkaloids were identified comparing their physical (specific optical rotation) and spectroscopic ( 1 H and 13 C NMR and ESI MS) properties with those already reported in the literature: for 1 by Lamoral-Theys et al (2009) [13] isolated from Stenbergia lutea, for 2 with those reported by Antoun et al (1993) [41] and Boit and Döpke (1960) [42] when isolated from Hymenocallis expansa and Hippeastrum aulicum, respectively. Alkaloids As previously reported, haemanthidine (7) was isolated as two 6-epimers [56] in a scalar ratio. The equilibrium between the two epimers was also reported for 6-hydroxycrinamine, but not for closely related crinine-type alkaloids such as 6α-hydroxycrinine and 6αhydroxybuphonisine.…”
Section: Resultssupporting
confidence: 59%
“…This result is in line with Sumarwoto's (2004) research that large bulbils have more food reserves to support the faster growth of porang plants. The results of research by Zaragoza-Puchol et al (2021) showed that whole bulbils in various sizes and pieces gave a high germination value (>90%), except for small bulbils, which gave a low percentage of germination (±60%).…”
Section: Germination Powermentioning
confidence: 98%
“…The Amaryllidaceae family is known for its ornamental potential and the ability to synthesize several alkaloids, including galantamine and lycorine, and potent acetylcholinesterase (AChE) inhibitors, used to alleviate the symptoms of Alzheimer’s Disease (AD) [ 4 ]. However, some species in this family are poorly represented, have a low multiplication rate [ 5 ] and are vulnerable or at risk of extinction [ 6 ]. Among the species in this family, Zephyranthes irwiniana (Ravenna) Nic.…”
Section: Introductionmentioning
confidence: 99%